2020
DOI: 10.3390/ijms21207527
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Iron-Bound Lipocalin-2 Correlates with Renal Recovery Markers Following Sepsis-Induced Kidney Damage

Abstract: During the course of sepsis in critically ill patients, kidney dysfunction and damage are among the first events of a complex scenario toward multi-organ failure and patient death. Acute kidney injury triggers the release of lipocalin-2 (Lcn-2), which is involved in both renal injury and recovery. Taking into account that Lcn-2 binds and transports iron with high affinity, we aimed at clarifying if Lcn-2 fulfills different biological functions according to its iron-loading status and its cellular source during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…It has been documented that LCN2 is an iron-carrier protein, and its biological activity depends on its iron-load and on where it is produced (renal tubules or macrophages), which defines its dual role in the development of kidney damage [ 60 , 61 , 62 ]. Iron-free LCN2 secreted by renal tubular epithelial cells has been associated with renal injury, and the expression and release of macrophage-derived iron-bound LCN2 has been linked to renal recovery [ 63 ]. Similarly, it has also been shown that adipose-tissue-derived LCN2 plays a critical role in causing both chronic and acute renal injury, but it is also essential for the progression of CKD in rodent and human models [ 46 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that LCN2 is an iron-carrier protein, and its biological activity depends on its iron-load and on where it is produced (renal tubules or macrophages), which defines its dual role in the development of kidney damage [ 60 , 61 , 62 ]. Iron-free LCN2 secreted by renal tubular epithelial cells has been associated with renal injury, and the expression and release of macrophage-derived iron-bound LCN2 has been linked to renal recovery [ 63 ]. Similarly, it has also been shown that adipose-tissue-derived LCN2 plays a critical role in causing both chronic and acute renal injury, but it is also essential for the progression of CKD in rodent and human models [ 46 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the application of LCN-2 diminishes renal injury and enables renal regeneration [147,151,175,193,194]. Recently, we found that LCN-2 fulfills different biological functions according to its iron-loading status and its cellular source during sepsis-induced kidney failure [195]. Interestingly, LCN-2 was produced and secreted from renal tubular epithelial cells in its iron-free form, which was associated with renal damage.…”
Section: Renal Iron Handling-mφ Versus Tubular Epithelial Cellsmentioning
confidence: 98%
“…A study by Urbschat et al ( 91 ) showed that mouse tubular epithelial cells (TECs) promoted the proliferation of epithelial cells by taking macrophage-derived iron-loaded Lcn-2. Mertens et al ( 92 ) concluded that the cellular source of Lcn-2 (TECs or macrophages) and its iron loading determine the biological function of Lcn-2 in cecal ligation and puncture (CLP)-induced kidney injury. At 24 h after CLP-induced kidney injury, elevated levels of iron-free Lcn-2 in TECs are primarily considered as markers of kidney injury, whereas elevated levels of iron-loaded Lcn-2 from macrophage sources are associated with markers of recovery ( 92 ) ( Fig.…”
Section: Macrophage-derived Mediators In Akimentioning
confidence: 99%